Use of Next Generation Sequencing and Synergy Susceptibility Testing in Diagnosis and Treatment of Carbapenem-Resistant Klebsiella pneumoniae Blood Stream Infection - Yuetian Yu; Fupin Hu; Cheng Zhu; Erzhen Chen; Liangjing Lu; Yuan Gao (Case Reports in Infectious Diseases)
Early diagnosis and appropriate treatment for carbapenem-resistant Klebsiella pneumoniae (CR-Kp) infection is a big challenge for clinicians due to its high mortality. Every effort has been made to improve its clinical outcomes. However, treatment according to synergy susceptibility testing has never been reported in the literature. We reported a 29-year-old systemic lupus erythematosus female with CR-Kp blood stream infection. We highlighted the identification by next generation sequencing and treatment according to synergy susceptibility testing in the case.